Basil sensitized ZnO photoelectrochemical cell for solar energy conversion. (2020) - Shiyani, T.; Mahapatra, S.K.; Banerjee, I.
Abstract: We have investigated the photoelectrochemical properties of basil sensitized ZnO hybrid photoelectrochemical cell (PEC) for solar energy conversion applications. ZnO thin film was fabricated on indium tin oxide (ITO) coated polyethylene terephtalate (PET) substrate using spin coating. A layer of natural basil dye was drop casted on zinc oxide (ZnO) thin film. The bandgap of ZnO is determined at about 3.29 eV. The protein complex of dye can be integrated with the semiconductor to enhance the light absorption and performance of the device. Natural dyes can absorb the light in a wide range of wavelengths. The photocurrents and photovoltages of the proposed flexible photoelectrochemical cell were measured using three electrode electrochemical method under the illumination of white light. The hybrid photoelectrode has been demonstrated for hybrid solar cell applications and achieved 0.45% energy conversion efficiency. The photocurrent and photovoltage are improved by 1.33 nA and 3.0 mV, respectively. The hybrid electrode also has been demonstrated for photoswitching applications. The basil/ZnO based hybrid devices may be useful to generate solar fuels to meet the energy demand in the future.